The Impact of Covid-19 Pandemic On The Results Of Village-Owned Enterprises (BUMDes) “Bersama Sei Rampah” - Merry Agnes (Yayasan Multidimensi Kreatif, 2023)
The outbreak of covid-19 coronavirus pandemic is now a social reality that must be faced by the world community, especially for the Nation of Indonesia. The fear of covid-19 coronavirus will affect the social attitudes of individual individuals, including villagers. Villages that have the potential of their villages to be managed to improve the welfare of villagers through village-owned enterprises (BUMDes). BUMDes is expected to be the main buffer for national economic growth during the Covid-19 Pandemic. This research is empirical legal research, this research is included in descriptive research. This research tells about the state of BUMDes